Performance and carcass characteristics of Nellore young bulls fed different sources of oils, protected or not from rumen degradation - Rosa, Bruna Laurindo [UNESP]; Sampaio, Alexandre Amstalden Moraes [UNESP]; Henrique, Wignez; Oliveira, Emanuel Almeida de [UNESP]; Pivaro, Thiago Martins [UNESP]; Andrade, Antonio Tadeu de [UNESP]; Fernandes, Alexandre Rodrigo Mendes (Sociedade Brasileira de Zootecnia, 2013)
The objective was to evaluate the addition of vegetable oils protected or not from rumen degradation in the diet of feedlot-finished young bulls and their effects on performance and carcass characteristics. Thirty-five Nellore males of 402.69±14.90 kg initial weight and 18±2 months of age were utilized. The animals were confined for 96 days, after 28 days of adaptation, and slaughtered at 532.17±30.25 kg. Experimental diets were: control (715 g total digestible nutrients - TDN/kg of dry matter - DM), with addition of soybean oil or fresh linseed oil, and with the addition of the same oils protected from rumen degradation (765 g TDN/kg DM). All diets were formulated with the same amount of protein and with a roughage:concentrate ratio of 40:60, with sugarcane as the only roughage. The addition of oil, regardless of the type and processing, resulted in greater body weight gain (1.17 and 1.41 kg/animal/day), better feed (0.11 and 0.14 kg weight gain/kg DM ingested) and protein efficiency (0.86 and 1.09 kg weight gain/kg crude protein ingested), heavier carcasses (280.3 and 298.0 kg), with better yield (54.5 and 55.5%) and thicker subcutaneous fat (5.1 and 7.5 mm backfat thickness) and with heavier prime cuts, for control diet and the other treatments, respectively. The use of soybean or linseed oil protected or not from rumen degradation only changed the intake of a few nutrients and carcass yield and depth. Thus the addition of energy sources in the diet is beneficial for finishing feedlot bulls. For this addition, either soybean or linseed oils can be used, and the processing of these oils is only useful to facilitate the mixing with the other ingredients of the diet.
Keywords: Feedlot; Linseed oil; Megalac-EÂ®; soybean oil; Sugarcane